Literature Review ; The Role of Human Resource Management in Employee Training on the Company's Competitive Advantage - nisa, abdatuz zahrotun; Sisiawan Putra, Riyan (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2022)
In a company, employees are one of the most important elements to achieve company goals, and the existence of globalization triggers the emergence of competition in various fields. With this, every company strives and is required to have the right and competent human resources to encourage business success so that they are able to compete with other companies. This study analyzes training on employee performance in the company, given the importance of the role of human resources in a company's competitive advantage. The purpose of this paper is to determine the extent of the development of research related to this topic. The method used in this study is a literature review. The results of the study can be seen that training has a significant effect on the company's competitive advantage. So that human resource management plays an important role in the realization of qualified employees and has optimal performance.